2022
DOI: 10.3390/diagnostics12092033
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Neutrophil to Lymphocyte Ratio, Monocyte to Lymphocyte Ratio, Platelet to Lymphocyte Ratio, and Platelet to Mean Platelet Volume Ratio in Periprosthetic Hip and Knee Infections: A Systematic Review and Meta-Analysis

Abstract: The current literature on the diagnosis of periprosthetic joint infection provides controversial evidence on the diagnostic accuracy of MLR, NLR, PVR, and PLR. Therefore, this critical literature search and meta-analysis was aimed to summarize the diagnostic accuracy of these biomarkers for the diagnosis of hip and knee prosthetic infection. According to the PRISMA flowchart, we searched MEDLINE, Scopus, and Web of Science, for studies on these ratios for diagnosing PJI. Sensitivity, specificity, positive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The predictive role of inflammatory biomarkers was analyzed and also demonstrated in the case of periprosthetic joint infection [ 39 , 40 , 41 , 55 , 56 , 57 ]. In the systemic review published by Festa et al [ 39 ], it was demonstrated that high values of MLR, NLR, and PLR are associated with the detection of hip and knee periprosthetic infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictive role of inflammatory biomarkers was analyzed and also demonstrated in the case of periprosthetic joint infection [ 39 , 40 , 41 , 55 , 56 , 57 ]. In the systemic review published by Festa et al [ 39 ], it was demonstrated that high values of MLR, NLR, and PLR are associated with the detection of hip and knee periprosthetic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hematological reports, based on neutrophil, monocyte, lymphocyte, and platelets total number: monocyte-to-lymphocyte ratio (MLR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic inflammatory index (SII), systemic inflammation response index (SIRI), and aggregate index of systemic inflammation (AISI), are routine inflammatory biomarkers, easy to use, with low costs. Moreover, the predictive role of these reports has been recently demonstrated in the literature in the case of cardiovascular pathology [ 24 , 25 , 26 , 27 ], pulmonary embolism [ 28 , 29 ], chronic kidney disease [ 30 , 31 , 32 ], the case of COVID-19 patients [ 33 , 34 , 35 , 36 , 37 , 38 ], as well as in the case of peri-prosthetic infection after total joint arthroplasty [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prosthetic joint infection (PJI) is one of the most severe complications after TKA [32]. Several studies have shown that PJI after knee surgery is associated with higher NRL and PLR levels [33][34][35][36][37]. Golge et al [38] found the value of 2.45 to be a cut-off point for infection after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…These biomarkers, in combination with plasma fibrinogen, ESR and CRP have been shown to increase the diagnostic performance [ 81 ]. Although a recent meta-analysis on the aforementioned ratios has shown a fair diagnostic value, it is not suggested as a screening tool [ 82 ]. More studies are needed to reach a consensus on these biomarkers.…”
Section: Methodsmentioning
confidence: 99%